Long-Term Depression of Striatal DA Release Induced by mGluRs via Sustained Hyperactivity of Local Cholinergic Interneurons - Mercuri, Nicola B.; Federici, Mauro; Rizzo, Francesca Romana; Maugeri, Lorenzo; D’Addario, Sebastian L.; Ventura, Rossella; Berretta, Nicola (Frontiers in Cellular Neuroscience, 2021)
The cellular mechanisms regulating dopamine release in the striatum have attracted much interest in recent years. By in vitro amperometric recordings in mouse striatal slices, we show that a brief (5 min) exposure to the metabotropic glutamate receptor agonist DHPG (50 µM) induces a profound depression of synaptic DA release, lasting over 1 hour from DHPG washout. This long-term depression is sensitive to glycine, which preferentially inhibits local cholinergic interneurons, as well as to drugs acting on nicotinic acetylcholine receptors and to the pharmacological depletion of released acetylcholine. The same DHPG treatment induces a parallel long-lasting enhancement in the tonic firing of striatal cholinergic interneurons, measured with multi-electrode array recordings. When DHPG is bilaterally infused in vivo in the mouse striatum, treated mice display an anxiety-like behavior, reminiscent of typical non-motor symptoms of Parkinson’s disease. Our results demonstrate that metabotropic glutamate receptors stimulation gives rise to a prolonged depression of the striatal dopaminergic transmission, through a sustained enhancement of released acetylcholine, due to the parallel long-lasting potentiation of striatal cholinergic interneurons firing. This plastic interplay between dopamine, acetylcholine and glutamate in the dorsal striatum may be involved in anxiety-like behavior, including Parkinson’s disease non-motor symptoms.